CLINIC MANAGEMENT: PROJECT PREPARATION APPLICATION (CIPEEX, 2022)
INTRODUCTION: THINK STRATEGICALLY IS TO DEFINE, STRUCTURE THE OBJECTIVES AND THE WAYS TO ACHIEVE A FINAL RESULT. IN HEALTH, PLANNING IS THE FUNCTION THAT ALLOWS IMPROVING THE PERFORMANCE, EFFICIENCY AND EFFECTIVENESS OF SERVICES IN FULFILLING THE PURPOSES OF PROTECTION, PROMOTION, RECOVERY AND REHABILITATION. OBJECTIVE: TO REPORT THE EXPERIENCE IN THE CONSTRUCTION OF AN APPLICATION PROJECT FOR THE BASIC HEALTH CARE NETWORK OF THE CITY OF ANÁPOLIS-GO, COLLABORATING WITH THE PROCESS OF PERMANENT EDUCATION OF THE NURSES TO BETTER SOLVE THE PRENATAL CARE NETWORK OF HABITUAL RISK. METHOD: A DESCRIPTIVE EXPERIENCE REPORT, WITH A QUALITATIVE APPROACH TO THE PROCESSES OF ELABORATION OF THE APPLICATION PROJECT IN THE POSTGRADUATE COURSE IN CLINICAL MANAGEMENT IN THE HEALTH REGIONS, IN THE YEAR 2017, OFFERED BY THE INSTITUTE OF EDUCATION AND RESEARCH (IEP) OF THE HOSPITAL SRIO IN THE PROCESS OF CONSTRUCTION OF THE APPLICATION PROJECT (PA), THE SITUATIONAL STRATEGIC THINKING (PES) IS USED TO ANALYZE THE CONTEXTS THAT INVOLVE HEALTH PRACTICES AND, IN PARTICULAR, THE PARTICIPANTS' WORK WORLD. IT BEGAN WITH THE IDEOLOGICAL OPENING THAT THERE IS NO SINGLE REALITY BUT RATHER DIFFERENT INTERPRETATIONS ABOUT A GIVEN CONTEXT. CONCLUSION: COMPLETION OF THE APPLICATION PROJECT, REPRESENTED BY THE ACTION PLAN, WAS GRATIFYING AS ALL WERE ABLE TO PARTICIPATE ACTIVELY IN THE CONSTRUCTION PROCESS IN STAGES PROPOSED BY THE COURSE AND, MAINLY, TO FOLLOW THE IMPLEMENTATION OF THIS IN THE MUNICIPALITY. REALIZING SOMETHING THAT WAS PREVIOUSLY JUST IDEAS AND, AFTER SYSTEMATIC PLANNING, MAKE THE MATERNAL HEALTH CARE OF FUTURE GENERATIONS OF PEOPLE FEASIBLE AND IMPACTFUL, GENERATES IMMENSE SATISFACTION.
Keywords: Health Projects; Permanent Education; Basic Attention